2018
DOI: 10.1177/0040563918766711
|View full text |Cite
|
Sign up to set email alerts
|

Gender Reassignment Surgery: A Catholic Bioethical Analysis

Abstract: There is no explicit authoritative Catholic teaching on gender reassignment surgery (GRS). Catholic bioethicists have debated the origin of gender dysphoria and the effectiveness of GRS. A further ethical question is whether some forms of GRS involve “mutilation in the strict sense.” The principle of totality does not apply to GRS as the reproductive organs are a cause of distress only because the object of distress. This analysis leaves open the status of GRS which does not compromise biological function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…13 A data extraction study conducted in USA using PubMed database suggested that health discrepancies experienced by trans-genders are somewhat deciphered by failure of medical school curricula to include trans-related health education which contributed to trans-inclusive healthcare obstacles. 14 Theological Studies at Digital Commons at Loyola Marymount University (LMU) on Christian bioethics stated that In Christian ethical frameworks, the body, in its natural state, is imbued with dignity and worth, sex and gender take on cosmological significance and many adherents of the Christian faith determine GRS (Gender Reassignment Surgery) to be immoral. [14][15][16][17][18] In a country like Pakistan where Transgender rights are not adequately guarded by law, changes in health policies are required to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 A data extraction study conducted in USA using PubMed database suggested that health discrepancies experienced by trans-genders are somewhat deciphered by failure of medical school curricula to include trans-related health education which contributed to trans-inclusive healthcare obstacles. 14 Theological Studies at Digital Commons at Loyola Marymount University (LMU) on Christian bioethics stated that In Christian ethical frameworks, the body, in its natural state, is imbued with dignity and worth, sex and gender take on cosmological significance and many adherents of the Christian faith determine GRS (Gender Reassignment Surgery) to be immoral. [14][15][16][17][18] In a country like Pakistan where Transgender rights are not adequately guarded by law, changes in health policies are required to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…14 Theological Studies at Digital Commons at Loyola Marymount University (LMU) on Christian bioethics stated that In Christian ethical frameworks, the body, in its natural state, is imbued with dignity and worth, sex and gender take on cosmological significance and many adherents of the Christian faith determine GRS (Gender Reassignment Surgery) to be immoral. [14][15][16][17][18] In a country like Pakistan where Transgender rights are not adequately guarded by law, changes in health policies are required to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%